NOD1 modulates decidual stromal cell function to maintain pregnancy in the early trimester. (8th August 2019) - Zhang, Yuanyuan; Zhang, Yuhui; Li, Chunmei; Fu, Shuai; Yang, Chunfeng; Song, Yan; Liu, Meilan; Wang, Zhenhua; Liang, Peili; Zhang, Jianping
Abstract : We sought to explore the functions and modulated factors of NOD1 in normal decidual stromal cells (DSCs) derived from the first trimester pregnancy and whether existed different expression of NOD1 between normal and unexplained recurrent pregnancy loss (URPL) in DSCs. Twenty‐six patients with normal pregnancies that required abortion and 12 URPL patients at first trimester were enrolled for the study. As a result, we found lower levels of NOD1 in the DSCs derived from URPL compared with those from normal early trimester pregnancy. Furthermore, increased NOD1 expression in the normal DSCs induced apoptosis and increased monocyte chemotactic protein‐1 (MCP‐1) and IL‐1β (interleukin 1 beta) secretion but decreased their invasion capacity. In addition, several cytokines such as IL‐1β, tumour necrosis factor‐alpha (TNF‐α), interferon‐gamma (IFN‐γ), and interleukin‐17 (IL‐17) were present at the maternal‐fetal interface in RPL and were found to regulate NOD1 expression in primary DSCs. Our study indicates that RPL may be associated with NOD1 aberrant expression in DSCs, which plays a significant role in maintaining pregnancy via infection control and regulation of immune responses that might affect the pregnancy outcome. We expect that our results will bring more comprehensively understanding about the connection between NOD1 and RPL for researchers.